The study of biosafety risk identification and analysis for facilities in biosafety level 3 laboratories - Lv, Bingwang; Zhou, Zhiyu; Wang, Jinsong; Niu, Qun; Shi, Yuchen; Sun, Yanbo; Zhao, Hongda; Lu, Dongsheng; Fan, Tao; Huang, Yang (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveThe aim of this study was to identify and analyze biosafety risk points in biosafety level 3 (BSL-3) laboratory facilities to bring awareness to the attention of administrative staff, reduce the biosafety risks, and improve the risk management.MethodsThe biosafety risk points in BSL-3 facilities were identified by literature searches and field research methods, and the identified biosafety risk points subsequently analyzed using the fault analysis event tree method.Results & conclusionThroughout the comprehensive screening and identification of biosafety risk points in BSL-3 laboratory facilities, risk assessments were performed to rank their seriousness. This will help effectively reduce the biosafety risk level of BSL-3 laboratory facilities.